Prevalence and predictors of peripheral neuropathy after breast cancer treatment. (14th August 2021) - Kamgar, Mandana; Greenwald, Mark K.; Assad, Hadeel; Hastert, Theresa A.; McLaughlin, Eric M.; Reding, Kerryn W; Paskett, Electra D.; Bea, Jennifer W.; Shadyab, Aladdin H.; Neuhouser, Marian L.; Nassir, Rami; Crane, Tracy E.; et al.
Abstract: Background: Many of the 3.8 million breast cancer survivors in the United States experience long‐term side effects of cancer therapy including peripheral neuropathy (PN). We assessed the prevalence and predictors of PN among women with breast cancer followed in the Women's Health Initiative's Life and Longevity After Cancer survivorship cohort. Methods: The study population included 2420 women with local (79%) or regional (21%) stage disease. Presence of PN was based on the reports of "nerve problems and/or tingling sensations" after treatment and PN severity was assessed using the Functional Assessment of Cancer Therapy‐Gynecologic Oncology Group/Neurotoxicity instrument. Logistic regression analysis was used to evaluate the socio‐demographic and clinical factors associated with PN prevalence and severity. Results: Initial breast cancer treatment included surgery‐only (21%), surgery and radiation (53%), or surgery and chemotherapy (±radiation) (26%). Overall, 17% of women reported PN occurring within days (30%), months (46%), or years (24%) after treatment and 74% reported ongoing symptoms at a median of 6.5 years since diagnosis. PN was reported by a larger proportion of chemotherapy recipients (33%) compared to those who had surgery alone (12%) or surgery+radiation (11%) ( p  < 0.0001). PN was reported more commonly by women treated with paclitaxel (52%) and docetaxel (39%), versus other chemotherapy (17%) ( p  < 0.0001). In multivariable analyses, treatment type (chemotherapy vs. none; OR, 95% CI: 3.31, 2.4–4.6), chemotherapy type (taxane vs. no‐taxane; 4.74, 3.1–7.3), and taxane type (paclitaxel vs. docetaxel; 1.59, 1.0–2.5) were associated with higher odds of PN. Conclusion: PN is an important long‐term consequence of taxane‐based chemotherapy in breast cancer survivors.